Analysis of the Level of Compliance with the Use of Personal Protective Equipment at PT XX Industrial and Construction Development - Nurfaizah Hasibuan; Susilawati Susilawati (Pusat Riset dan Inovasi Nasional, 2024)
The industrial and construction development sector is a sector that really needs workers in the field, therefore with the work in the field, PT must always be vigilant under any circumstances to keep workers from work accidents. By using personal protective equipment to workers. The government has considered the issue of protection for labor, namely through Law No. 1 of 1970 concerning Labor Safety Work safety equipment is equipment that can protect workers from workplace hazards. Compliance with the use of personal protective equipment in PT XX Industrial and Construction Development has been very good. This research uses qualitative research methods. This research was conducted by interviewing workers of pt. XX Industrial and Construction Development. The focus of this study is on the analysis of the level of compliance with the use of personal protective equipment. The population taken was 4 informants, namely 3 workers and 1 safety man. Data taken includes interviews, observations, documentation and data recording. The knowledge of workers in PT XX Industrial and Construction Development is very good, compliance with the use of worker personal protective equipment is also quite good, the personal protective equipment facilities provided by PT are very complete, and the supervision provided by PT is also very routine and has sanctions for those who are caught not wearing PPE in the form of reprimands.